Key Theological Deductions in al-Imām al-Jushamī 's Exegesis: An Analytical Study in the First Part of the Noble Qurʼān as a Model - Souilah Akram Abdel Bari; Samir El Hosry; Abdelali Bey Zekkoub (MAQOLAT: Journal of Islamic Studies, 2024)
This research aims to investigate the doctrinal deductions in the interpretation of al-Imām al-Jushamī, , which he mentioned within the limits of the research, and to study them critically from the beginning of Surat Al- Fātiḥah to the end of the first part of Surat Al-Baqarah. The research problem underscores that these doctrinal deductions have not been systematically compiled or thoroughly studied, although some have been explored by scholars . While there are advantages to his deductions, there are also drawbacks. This research seeks to clarify Al-Hakim Al-Jashmi’s doctrinal deductions, highlighting their strengths, weaknesses, and discrepancies. The researcher employed an inductive and analytical approach, identifying doctrinal deduction areas and consolidating them, followed by examination, analysis, and criticism based on abstraction in ideas and rulings. Several findings were reached, notably that deduction is  a science that tolerates right and wrong, and that deviation in interpretation and doctrine is one of the main reasons for error in deduction, as well as Al-Hakim Al-Jashmi paid attention to the aspect of deduction in his interpretation, especially in the aspect of belief. He summarized and elucidated the views of his predecessors to the best of his ability, while also transmitting insights from those who preceded him and were influenced by them.